1994
DOI: 10.1267/ahc.27.67
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Radioautographic Study on 3H-Leucine Uptake of Peri- and Tele-Insular Acinar Cells of the Pancreas in Normal and Streptozotocin-Diabetic Mice.

Abstract: The uptake of 3H-leucine by peri-and tele-insular acinar cells of the pancreas was analyzed quantitatively 60 min after the intraperitoneal injection of 3H-leucine in normal and streptozotocin-diabetic mice. A large tissue sample was analyzed and the grain density was counted with a color image analyzer equipped with a computer. The radioactivity was expressed as number of silver grains per acinar cell as well as per unit area of acinar tissue. In normal mice, the radioactivity in peri-insular acinar cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…While most of the studies showed a positive effect of insulin the results are complicated by changes in the precursor pool or changes in the levels of mRNAs. When protein synthesis in mice was quantitated by autoradiography, there was more incorporation into peri-insular acinar cells then into tele-insular acinar cells (7). This difference was lost following treatment with streptozotocin and the authors ascribed it to insulin.…”
Section: Protein Synthesismentioning
confidence: 99%
“…While most of the studies showed a positive effect of insulin the results are complicated by changes in the precursor pool or changes in the levels of mRNAs. When protein synthesis in mice was quantitated by autoradiography, there was more incorporation into peri-insular acinar cells then into tele-insular acinar cells (7). This difference was lost following treatment with streptozotocin and the authors ascribed it to insulin.…”
Section: Protein Synthesismentioning
confidence: 99%